Performanee of strawberry (Fragariax ananassa) cultivars under sub-tropics of Meghalaya - Singh, Akath; Patel, R K; De, L C; Periera, Lolly S (The Indian Journal of Agricultural Sciences, 2008)
A study was conducted during 2005-07 at Umiam, Meghalaya to evaluate 25 strawberry (Fragariax ananassa Duch.) cultivars under sub-tropic conditions of Meghalaya. Cultivars 'Camarosa' and 'Cherigent 5' showed earliest flowering and they took only 91 and 94 days, respectively after planting. The fruits harvested/plant was highest in 'Dana' (24.9), followed by 'Elista' (23.3) and 'Blakemore' (22.6) but its size was maximum in 'Camarosa', followed by 'Ofra' and 'Sweet Charlie'. The highest fruit yield/plant (245.2 g) was produced by 'Camarosa', followed by 'Ofra' (228.5g), but fruit weight was higher in 'Camarosa' (17.2 g) and 'Sweet Charlie' (14.2 g). Fruit quality in terms of TSS (14.2 degree Brix), anthocyanin content (125.4 mg/100 g), ascorbic acid content (107.5 mg/lO0 g) and total sugars (8.38%) was highest in 'Ofra', followed by 'Chandler'.